Humanized Mouse Models for the Study of Human Malaria Parasite Biology, Pathogenesis, and Immunity - Minkah, Nana K.; Schafer, Carola; Kappe, Stefan H. I. (Frontiers in Immunology, 2018)
Malaria parasite infection continues to inflict extensive morbidity and mortality in resource-poor countries. The insufficiently understood parasite biology, continuously evolving drug resistance and the lack of an effective vaccine necessitate intensive research on human malaria parasites that can inform the development of new intervention tools. Humanized mouse models have been greatly improved over the last decade and enable the direct study of human malaria parasites in vivo in the laboratory. Nevertheless, no small animal model developed so far is capable of maintaining the complete life cycle of Plasmodium parasites that infect humans. The ultimate goal is to develop humanized mouse systems in which a Plasmodium infection closely reproduces all stages of a parasite infection in humans, including pre-erythrocytic infection, blood stage infection and its associated pathology, transmission as well as the human immune response to infection. Here, we discuss current humanized mouse models and the future directions that should be taken to develop next-generation models for human malaria parasite research.